The Australasian Diabetes Data Network: first national audit of children and adolescents with type 1 diabetes. Issue 3 (20th February 2017) - Phelan, Helen; Clapin, Helen; Bruns, Loren; Cameron, Fergus J; Cotterill, Andrew M; Couper, Jennifer J; Davis, Elizabeth A; Donaghue, Kim C; Jefferies, Craig A; King, Bruce R; Sinnott, Richard O; Tham, Elaine B; et al.
Abstract: Objectives: To assess glycaemic control, anthropometry and insulin regimens in a national sample of Australian children and adolescents with type 1 diabetes. Design: Cross‐sectional analysis of de‐identified, prospectively collected data from the Australasian Diabetes Data Network (ADDN) registry. Setting: Five paediatric diabetes centres in New South Wales, Queensland, South Australia, Victoria and Western Australia. Participants: Children and adolescents (aged 18 years or under) with type 1 diabetes of at least 12 months' duration for whom data were added to the ADDN registry during 2015. Main outcome measures: Glycaemic control was assessed by measuring haemoglobin A1c (HbA1c ) levels. Body mass index standard deviation scores (BMI‐SDS) were calculated according to the CDC‐2000 reference; overweight and obesity were defined by International Obesity Task Force guidelines. Insulin regimens were classified as twice‐daily injections (BD), multiple daily injections (MDI; at least three injection times per day), or continuous subcutaneous insulin infusion (CSII). Results: The mean age of the 3279 participants was 12.8 years (SD, 3.7), mean diabetes duration was 5.7 years (SD, 3.7), and mean HbA1c level 67 mmol/mol (SD, 15); only 27% achieved the national HbA1c target of less than 58 mmol/mol. The mean HbA1c level was lower in children under 6 (63 mmol/mol) than in adolescents (14–18 years; 69 mmol/mol). Mean BMI‐SDS for all participants was 0.6 (SD, 0.9); 33% of the participants were overweight or obese. 44% were treated with CSII, 38% with MDI, 18% with BD. Conclusions: Most Australian children and adolescents with type 1 diabetes are not meeting the recognised HbA1c target. The prevalence of overweight and obesity is high. There is an urgent need to identify barriers to achieving optimal glycaemic control in this population.